AB0738 DUAL NEUTRALISATION OF INTERLEUKIN (IL)–17A AND IL–17F WITH BIMEKIZUMAB IN MODERATE-TO-SEVERE PLAQUE PSORIASIS: 60-WEEK RESULTS FROM A RANDOMISED, DOUBLE-BLINDED, PHASE 2B EXTENSION STUDY. (June 2019) - Blauvelt, Andrew; Papp, Kim a.; Merola, Joseph F.; Gottlieb, Alice B.; Cross, Nancy; Madden, Cynthia; Wang, Maggie; Cioffi, Christopher; Griffiths, Christopher E.M.
Abstract : Background: Psoriasis is a chronic, systemic, immune-mediated inflammatory disease associated with prominent skin manifestations. One in four patients with psoriasis also has psoriatic arthritis, 1 with skin disease preceding joint manifestations in most patients. 2 interleukin (IL)-17F shares structural homology and pro-inflammatory function with IL-17A. Preclinical and early clinical data support dual neutralisation of IL-17F, together with IL-17A, as a novel targeting approach for the treatment of immune-mediated inflammatory diseases. Bimekizumab, a monoclonal antibody that potently and selectively neutralises both IL-17A and IL-17F, is in development for the treatment of psoriasis, psoriatic arthritis and ankylosing spondylitis. 3–5 in the 12-week BE aBLE 1 study (NCT02905006 ), bimekizumab provided rapid and substantial clinical improvements in patients with moderate-to-severe plaque psoriasis, with a safety profile consistent with previous bimekizumab studies. 3 Objectives: The objectives of this Phase 2b extension study (BE aBLE 2; NCT03010527 ) were to assess the long-term safety and efficacy of subcutaneous bimekizumab every four weeks for an additional 48 weeks (60 weeks' total exposure). Methods: BE aBLE 1 responders (≥90% reduction in Psoriasis area Severity index [PASI90] at Week 12) receiving placebo or bimekizumab 64mg, 160mg, 160mg (320mg loading dose [LD]) remained on the same dose; non-responders (<PASI90 at Week 12) were re-assigned from placebo/bimekizumab 64mg to 160mg or from 160mg/160mg (LD) to 320mg. Patients previously receiving bimekizumab 320mg/480mg received 320mg. The primary variable was the exposure-adjusted incidence rate (EAIR) of treatment-emergent adverse events (TEAEs); efficacy assessments were secondary. Results: 217 patients were enrolled. Across all doses, BE aBLE 1 responders generally maintained complete or almost complete skin clearance for up to an additional 48 weeks: PASI90: 80−100%, non–responder imputation (93−100%, observed); PASI100: 70−83% (80−96%); investigator's Global assessment: 78−100% (98−100%). PASI100 was achieved by 33−76% (40−82%) of non-responders (Week 48). EAIR of TEAEs was 206.1/100 patient-years (n=184/217 [85%]). EAIR of serious TEAEs was 6.2/100 patient-years (n=15/217 [7%]); no serious TEAE was reported by >1 patient. The most frequent TEAEs were oral candidiasis and nasopharyngitis. No cases of suicidal ideation/behaviour, major adverse cardiac events, or inflammatory bowel disease were reported. No new safety findings were observed. Conclusion: Nearly all BE aBLE 1 responders completing 60 weeks of bimekizumab treatment maintained complete or almost complete skin clearance, with a safety profile consistent with previous studies. 3 References: 1 . Alinaghi et al. J am acad Dermatol 2019;80:251-65; 2 . Gladmann et al. Ann Rheum Dis 2005;64:ii14–17; 3 . Papp et al. J am acad Dermatol 2018;79:279–286; 4 . Van der Heijde et al. Ann Rheum Dis 2018;77:A70; 5 . Ritchlin et al. Arthritis Rheumatol 2018;70(S10):L17 Acknowledgement: The study was funded by UCB Pharma. Disclosure of interests: Andrew Blauvelt Grant/research support from: abbVie, aclaris, akros, allergan, almirall, amgen, Boehringer ingelheim, Celgene, Dermavant, Dermira inc, Eli Lilly and Company, Galderma, Genentech/Roche, GlaxoSmithKline, Janssen, LEO, Meiji, Merck Sharp & Dohme, Novartis, Pfizer, Purdue Pharma, Regeneron, Revance, Sandoz, Sanofi Genzyme, Sienna Pharmaceuticals, Sun Pharmaceuticals, UCB Pharma, Valeant, Vidac, Consultant for: abbVie, aclaris, akros, allergan, almirall, amgen, Boehringer ingelheim, Celgene, Dermavant, Dermira inc., Eli Lilly and Company, Galderma, Genentech/Roche, GlaxoSmithKline, Janssen, LEO, Meiji, Merck Sharp & Dohme, Novartis, Pfizer, Purdue Pharma, Regeneron, Revance, Sandoz, Sanofi Genzyme, Sienna Pharmaceuticals, Sun Pharmaceuticals, UCB Pharma, Valeant, Vidac., Speakers bureau: Janssen, Regeneron, Sanofi Genzyme, Kim a. Papp Grant/research support from: abbVie, akros, allergan, amgen, anacor, arcutis, astellas, Baxalta, Boehringer ingelheim, Bristol-Meyers Squibb, Can-Fite Biopharma, Celgene, Coherus, Dermira, Dow Pharma, Eli Lilly, Galderma, Genentech, Gilead, GlaxoSmithKline, inflaRx GmbH, Janssen, Kyowa Hakko Kirin, LEO, MedImmune, Merck (MSD), Merck-Serono, Moberg Pharma, Novartis, Pfizer, PRCL Research, Regeneron, Roche, Sanofi-Aventis/Genzyme, Takeda, UCB Pharma, Valeant/Bausch Health, Consultant for: abbVie, akros, amgen, arcutis, astellas, astraZeneca, Baxalta, Baxter, Boehringer ingelheim, Bristol-Meyers Squibb, Can-Fite Biopharma, Celgene, Coherus, Dermira, Dow Pharma, Eli Lilly, forward Pharma, Galderma, Genentech, Janssen, Kyowa Hakko Kirin, LEO, Meiji Seika Pharma, Merck (MSD), Merck-Serono, Mitsubishi Pharma, Novartis, Pfizer, PRCL Research, Regeneron, Roche, Sanofi-Aventis/Genzyme, Takeda, UCB Pharma, Valeant/Bausch Health, Speakers bureau: abbVie, amgen, astellas, Celgene, Eli Lilly, Galderma, Janssen, Kyowa Hakko Kirin, LEO, Merck (MSD), Novartis, Pfizer, Sanofi-Aventis/Genzyme, Valeant/Bausch Health, Joseph F. Merola Consultant for: Biogen IDEC, abbvie, amgen, Eli Lilly and Company, Novartis, Pfizer, Janssen, UCB, Samumed, Celgene, Sanofi Regeneron, Merck, and GSK, alice B. Gottlieb Grant/research support from: incyte Corporation, Janssen Ortho inc, Lilly ICOS LLC, Novartis, UCB, XBiotech, Consultant for: abbVie, BMS, Celgene Corporation, Dermira, incyte Corporation, Janssen Biotech, Janssen Ortho inc, LEO Pharma, Lilly ICOS LLC, Novartis, Sun Pharmaceuticals Ltd, UCB, Speakers bureau: abbVie, Eli Lilly and Company, Janssen Biotech, Nancy Cross Employee of: UCB Biosciences inc, Cynthia Madden Shareholder of: UCB Biosciences inc, Employee of: UCB Biosciences inc, Maggie Wang Employee of: UCB Biosciences inc, Christopher Cioffi Shareholder of: UCB Biosciences inc, Employee of: UCB Biosciences inc, Christopher E.M. Griffiths Grant/research support from: abbVie, Celgene, LEO, Lilly, Janssen, Novartis, Pfizer, Sandoz, UCB Pharma, Speakers bureau: abbVie, almirall, Bristol-Meyers Squibb, Celgene, Galderma, Janssen, Lilly, Novartis, Pfizer, Sandoz, UCB Pharma